Spatial Impact of Transportation Infrastructure: A Spatial Econometric CGE Approach - Zhenhua Chen (European Regional Science Association (ERSA), 2013)
Transportation infrastructure plays an important role in regional economic development both in the stimulation of growth and as a response to output expansion. However, measuring these effects quantitatively has been a challenge due to the complicated impact mechanisms of transportation infrastructure. This complication is due to two reasons: first, regional impacts of transportation infrastructure are achieved through a mechanism that involves both a demand influence through the variation of transportation price and a supply influence implemented through the variation of transportation cost; second, impacts of transportation are usually evaluated in a regional context where the presence of unobserved local or regional variables may give rise to spatial autocorrelation. As a result, impact analysis may become biased and spurious. This study develops a new method called Spatial Econometric Computable General Equilibrium (SECGE) model, which integrates both spatial econometrics with equilibrium modeling techniques to improve the effectiveness of impact analysis on transportation infrastructure. This study differs from previous studies in the following three aspects: First, through a spatial autocorrelation test, the presence of spatial dependence is observed and confirmed among the elasticities of factor substitution in the US. To deal with spatial dependence, spatial panel econometric techniques are introduced to estimate the elasticity of factor substitution of different sectors for the Constant Elasticity of Substitution (CES) production function with consideration of spatial direct and indirect effects. Second, transportation impact analysis is conducted under different scenarios of general equilibrium frameworks. Unlike partial equilibrium analysis, general equilibrium analysis allows researchers to obtain much comprehensive understanding of transportation infrastructure?s impacts given its consideration of interactions between the demand and the supply. The study validates the method by comparing traditional equilibrium simulation without controlling for spatial dependence and the new equilibrium simulation with consideration of spatial dependence. The comparison allows researchers to justify spatial impacts of transportation infrastructure. Third, the study is conducted with a focus on multiple modes of transportation that includes road, rail, air, transit, pipeline and water transportation. Unlike a unimodal perspective, the perspective of multiple modes is essential to achieve a comprehensive understanding of the transportation infrastructure systems. It also enables us to compare impacts between different types of infrastructures and understand the relative importance of transportation investment by mode. The study confirms that the US highway and streets plays a dominant role among all transportation infrastructure systems in economic development while public transit and passenger transportation only plays the least important role among the systems. The result general equilibrium analysis also shows a difference between using spatial econometric estimates and traditional OLS estimates. Although the differences are relatively small in this aggregate case study, implications for more sensitive disaggregated regional models are clear.
Keywords: C23; R11; R42; R53; 330